Tradução e adaptação da escala de dependência de substâncias do Millon Clinical Multiaxial III para o Brasil - Rocha, Hannia Roberta Rodrigues Paiva da (2011)
Millon describes the normal personality by means of adaptation styles that are effective in normal environments and personality disorders such as unadapted operating styles. To operacionalize his theoretical model, Millon has built several instruments, including the Millon Clinical Multiaxial Inventory III (MCMI-III), wich consists of a self report inventory composed by 175 true or false response items, containing four verification scales, and others scales wich evaluates 14 personality patterns and 10 clinical syndromes. The Substance Dependence scale (T) is placed along with Clinical Syndromes scales. This research is justified by the lack of a Brazilian instrument to assess personality psychopathological aspects, and aims to translate and semantically adapt the MCMI-III to the Brazilian context, checking validity elements of the Substance Dependence scale, and developing a computer application for assisting the evaluation of assessment results. To this intent, 2.588 individuals data was collected, male and female, aged between 18 and 85 years, characterized as belonging to a clinical or non-clinical group, who took part in the survey via the internet or in person. Respondents completed the MCMI-III, a socio-demographic questionnaire and a subgroup also answered to the Goldberg General Health Questionnaire (GHQ). Besides descriptive statistics, we performed the analysis using the Student t test, principal components analysis and internal consistency. Despite difficulties related to translating very specific English terms, the assessment by judges, experts on Millon´s theory, and the back translation, attested the adequacy of the Brazilian version. Factorial analysis indicated the grouping of translated T scale items into three factors (social activities prejudice, lack of impulse control, and oppositional behavior), by presenting a single item on a fourth factor (apparently related to seeking pleasurable stimuli). The Cronbach alpha for this set of items was 0,82, indicating an acceptable scale reliability. The data analysis resulted in distinction of scores between clinical and non-clinical groups and between men and women; the relationship between high scores on the scale T and the other scales; scores of drug users according to the declared used substance; and the relationship between high scores on T and the verification of disorder or risk on GHQ mental health factor, indicating the instrument´s adequate sensistivity in identifying psychopathologies and the relationship between the different disorders or psychopathological personality patterns. Although further studies are necessary to develop the scores transformation factors, the computerized correction tool was adequate.